Kinetic studies of esterification of rosin and pentaerythritol - Hardhianti, Meiga Putri Wahyu; Rochmadi, Rochmadi; Azis, Muhammad Mufti (MDPI, 2022)
Esterification of rosin with pentaerythritol produces rosin pentaerythritol ester (RPE) which is widely used in paint, coating, and pressure-sensitive and hot-melt adhesive industries. Although RPE has excellent valuable applications and has been industrially produced, studies on the reaction kinetics have not been widely reported in the present literature. This work proposed a kinetic study of RPE synthesis by including a series of consecutive reactions forming mono-, di-, tri-, and tetra-ester with decarboxylation of rosin as a side reaction in the kinetics model. For esterification, the reaction rates were determined by the second-order kinetic model. The first-order kinetic order was proposed for decarboxylation. Kinetic experiments were performed at a temperature range of 260◦C to 290◦C. The initial molar ratio of pentaerythritol to rosin (in the mole of OH/COOH) used was between 0.8 and 1.2. A small amount of samples were withdrawn in certain time interval. The sample was analyzed to evaluate their acid and saponification number. Afterward, those experimental data were used to simulate and validate the proposed kinetic model. In general, the proposed model could capture the experimental data well. The resulting activation energies ranged from 65.81 to 129.13 kJ mol−1 for esterification and 233.00 kJ mol−1 for decarboxylation. This model also offers a new insight that correlates well with tetra-ester formation and the softening point. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.